Effective Risk Assessment for Distal Radius Fractures: A Rigorous Multivariable Regression Analysis, Using a Novel 8-Item Modified Frailty Index - Momtaz, David; Ghali, Abdullah; Ahmad, Farhan; Gonuguntla, Rishi; Kotzur, Travis; Wang, Rebecca J.; Ghilzai, Umar; Abbas, Adam; Wu, Chia (Journal of Wrist Surgery, 2023)
Introduction Distal radius fractures (DRFs) are among the most common orthopaedic injuries. The prevalence of DRFs is increasing across all age groups but remains the second most common fracture in the elderly. The modified frailty index (MFI) often predicts morbidity and mortality in orthopaedic injuries. This study aims to determine the predictive value of MFI on complication rates following DRF and the patient length of stay and discharge outcomes.Methods We utilized our MFI to perform a retrospective analysis of the American College of Surgeons National Surgical Quality Improvement Program database.Results In a total of 22,313 patients, the average age was 46 ± 16. An increase in MFI led to an increase in the odds ratio of readmission and reoperation (p < 0.001). MFI predicted complications, doubling the rate as the score increased from 1 to 2 (p < 0.001). An MFI of 2 also led to a delayed hospital stay of 5 days (p < 0.001), as well as an increase in the odds of patients not being sent home at discharge (p < 0.001). Finally, life-threatening complications were also predicted with an increased MFI, the odds of a life-threatening complication increasing 488.20 times at an MFI of 3 (p < 0.001).Discussion and Conclusion While surgical decision-making for frail patients with DRFs remains contentious, this novel 8-item MFI score was significantly associated with the probability of hospital readmission/reoperation, postoperative complications, and delayed hospital length of stay. Three new parameters were incorporated into our 8-item score compared with the conventional 5; hypoalbuminemia status (< 3.5 mg/dL), previous diagnosis of osteoporosis, and severe obesity (body mass index > 35) enhancing its sensitivity. Future studies are warranted for its prospective utility in ruling out postsurgical comorbidity.
Keywords: distal radius fracture; modified frailty index; risk assessment; length of stay